A polylactic acid non‐woven nerve conduit for facial nerve regeneration in rats. (11th June 2012) - Matsumine, Hajime; Sasaki, Ryo; Yamato, Masayuki; Okano, Teruo; Sakurai, Hiroyuki
Abstract This study developed a biodegradable nerve conduit with PLA non‐woven fabric and evaluated its nerve regeneration‐promoting effect. The buccal branch of the facial nerve of 8 week‐old Lewis rats was exposed, and a 7 mm nerve defect was created. A nerve conduit made of either PLA non‐woven fabric (mean fibre diameter 460 nm), or silicone tube filled with type I collagen gel, or an autologous nerve, was implanted into the nerve defect, and their nerve regenerative abilities were evaluated 13 weeks after the surgery. The number of myelinated neural fibres in the middle portion of the regenerated nerve was the highest for PLA tubes (mean ± SD, 5051 ± 2335), followed by autologous nerves (4233 ± 590) and silicone tubes (1604 ± 148). Axon diameter was significantly greater in the PLA tube group (5.17 ± 1.69 µm) than in the silicone tube group (4.25 ± 1.60 µm) and no significant difference was found between the PLA tube and autograft (5.53 ± 1.93 µm) groups. Myelin thickness was greatest for the autograft group (0.65 ± 0.24 µm), followed by the PLA tube (0.54 ± 0.18 µm) and silicone tube (0.38 ± 0.12 µm) groups, showing significant differences among the three groups. The PLA non‐woven fabric tube, composed of randomly‐connected PLA fibres, is porous and has a number of advantages, such as sufficient strength to maintain luminal structure. The tube has demonstrated a comparable ability to induce peripheral nerve regeneration following autologous nerve transplantation. Copyright © 2012 John Wiley & Sons, Ltd.